Aprendizaje significativo en niños y niñas del primer año de educación básica de la escuela Provincia de El Oro del cantón El Guabo parroquia de Tíllales. 2014 - 2015. - Hermida Villa, Andrea Elizabeth (2015)
In the package of reforms introduced by the Ecuadorian State in the field of education it is perhaps the most important, The special attention is given to children of school age in order to pay more attention at an early age to prepare them to participate actively and responsibly in their own educational development of children, it is considered paramount changing educational paradigms by applying meaningful learning in early childhood education, raised by various studies of the subject and object of study from different disciplines that undertake as pedagogy, psychology, didactics and artistic activity, fun and music.